Anatomical aspects of the lacrimal gland of the tufted capuchin (Cebus apella) - Veiga Neto, E. R.; Tamega, O. J. [UNESP]; Zorzetto, N. L. [UNESP]; DALLPAI, V. [UNESP] (Cambridge University Press, 1992)
In the tufted capuchin (Cebus apella) the main lacrimal gland is composed of 2 distinct portions with an intraorbital and extraorbital localisation, interconnected by a bridge of glandular tissue which crosses the lateral orbital wall through the lateral orbital fissure located in the sphenozygomatic suture. The intraorbital lacrimal gland is flattened and extremely thin, with a variable outline. It lies on the upper and outer third of the globe of the eye, and the aponeurosis and the belly of the lateral rectus muscle, extending antero-posteriorly from the upper lateral angle of the orbit midway along the orbital cavity. The extraorbital lacrimal gland is compact, halfmoon-shaped, with 3 surfaces, 3 borders and 2 extremities. It lies in the temporal fossa between the temporalis muscle and the temporal surface of the zygomatic bone, fitting into a depression in this bone, and totally surrounded by adipose tissue. The secretory cells have a flocculent appearance and either low or high density. They possess a basal region containing the nucleus and rich in granular endoplasmic reticulum, and an apical region filled with secretory granules varying in size, form and density.